A search advantage for dynamic same-race and other-race faces. Issue 4 (3rd July 2017) - Butcher, Natalie; Lander, Karen; Jagger, Rachel
ABSTRACT: Previous work has found faster and more accurate recognition of faces learned from moving sequences than from static images. However, it is unclear whether the motion advantage can be generalized to other-race face learning. In two experiments, we examined the motion advantage for same-race and other-race faces in the context of a delayed visual search task and investigated the importance of face repetitions and clip length at learning. Participants learned faces as a static image or a moving clip and then searched for these target faces in visual arrays. Same-race target faces were located faster and more accurately than other-race targets. A dynamic search advantage was revealed for both same-race and other-race faces, whereby search latencies were shorter, and accuracy higher, for faces learned in motion. Furthermore, differing clip lengths and face repetitions during familiarization yielded the same dynamic advantage (Experiment 2), suggesting that motion provides a robust and valuable cue for the identification of both same-race and other-race faces.